1999
DOI: 10.1002/(sici)1097-4628(19991024)74:4<866::aid-app13>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

?-Irradiated poly(tetrafluoroethylene) particle-filled low-density polyethylene. I. Effect of silane coupling agents on mechanical, thermal, and morphological properties

Abstract: Poly(tetrafluoroethylene) (PTFE) scraps were recovered as a filler material for low-density polyethylene (LDPE) after they were degraded by Co-60 ␥-rays under atmospheric conditions to make small-size powder. The powder PTFE, which was called secondary PTFE (2°-PTFE), was melt mixed with LDPE and then extruded to obtain 200 m films. The mechanical and thermal properties and also the morphology of the fractured surface of these 2°-PTFE-filled LDPE were studied. It was found that the addition of 2°-PTFE resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Surface morphology of PP/HDPE blend was observed with a JSM‐5910 scanning electron microscope (SEM). Before observation, samples were treated with etching agent (a solution of KMnO 4 , 1.3 wt %; H 2 SO 4 , 65.8 wt %; H 3 PO 4 , 32.9 wt %) for 24 h, then washed out the etching agent thoroughly with H 2 O 2 and H 2 O, dried at room temperature and sputter‐coated with gold. Impact fracture surface of PP/HDPE blends was directly observed by SEM.…”
Section: Methodsmentioning
confidence: 99%
“…Surface morphology of PP/HDPE blend was observed with a JSM‐5910 scanning electron microscope (SEM). Before observation, samples were treated with etching agent (a solution of KMnO 4 , 1.3 wt %; H 2 SO 4 , 65.8 wt %; H 3 PO 4 , 32.9 wt %) for 24 h, then washed out the etching agent thoroughly with H 2 O 2 and H 2 O, dried at room temperature and sputter‐coated with gold. Impact fracture surface of PP/HDPE blends was directly observed by SEM.…”
Section: Methodsmentioning
confidence: 99%
“…The other details of the 2°-PTFE blended with LDPE were discussed in our previous study. 21 The LDPE was supplied by the Turkish Petrochemical Industry G03-5-PETKIM. The melt flow index and density of the polymer were 0.3 g/10 min and 0.921 g/mL, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the film preparation were discussed in our previous study. 21 SEM analysis was made on both monomer grafted 2°-PTFE powder samples and tensile fractured surfaces of the monomer grafted 2°-PTFE powder filled LDPE film samples at various magnifications after gold plating by using a Jeol JSM-6400 SE microscope.…”
Section: °-Ptfe Filled Ldpe Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Both heat treatment and grinding processes in amorphous PET inevitably increased thermal decomposition and further oxidation. Zimmerman 25 showed that an extensive autocatalytic reaction by hydrolytic cleavage of polyester chains resulted in carboxyl groups under isothermal heating. Similar results were reported earlier by Buxbaum,26 and the degradation mechanism was also reviewed by Jabarin.…”
Section: Sem Studiesmentioning
confidence: 99%